City Focus: A web-based interactive 2D and 3D GIS application to find the best place in a city, using open data and open source software - Arias Muñoz, Carolina; Corti, Simone; Molinari, Monia; Oxoli, Daniele; prestifilippo, Gabriele (PeerJ Preprints, 2016)
City Focus is a web-based interactive 2D and 3D GIS application to find the best place in a city to live as well as to pass shorter staying. The user can select among different criteria and decide their importance by assigning weights to each of them. The application provides thematic maps displaying insights on the places which better fit the user’s preferences. The resulting map is computed through map algebra by means of Web Coverage Processing Service WCPS provided by RASDAMAN Database Management System. Data visualization is mainly based on NASA Web WorldWind open-source virtual globe. The app exploits exclusively open data as well as Free and Open Source Software (FOSS) for its implementation by enabling continuous improvements while minimizing development costs.
Keywords: Open data; Free and Open Source Software; NASA Web WorldWind; RASDAMAN